Kepuasan Pasien BPJS di Poliklinik Ortopedi RSUD KiSA Depok - Bintang Muharam; Bangga Agung Satrya; Dina Sonia; Noor Yulia; Muhammad Fuad Iqbal (Jurnal Manajemen Informasi dan Administrasi Kesehatan (JMIAK), 2026)
Patient satisfaction is a crucial indicator of healthcare quality within the JKN–BPJS ecosystem, particularly in orthopedic outpatient services characterized by musculoskeletal caseloads and high visit volumes. This study aims to measure the level of patient satisfaction among BPJS Health users at the Orthopedic Clinic at KiSA Hospital in Depok City using the SERVQUAL methodology, which encompasses five quality dimensions (tangible, reliability, responsiveness, assurance, empathy). The study design was quantitative descriptive with 95 respondents aged 17 years and over. Data were collected through questionnaires and observations from November 2024–April 2025, then analyzed descriptively using SPSS. Overall, 55% of respondents expressed satisfaction and 45% expressed dissatisfaction. The Empathy dimension had the highest satisfaction (83%) for the indicator of doctors considering the patient's condition during check-ups, and the Physical Evidence dimension elicited the highest dissatisfaction regarding parking availability (80%). The Reliability dimension stood out through two strong indicators: accurate diagnosis and doctor speed–accuracy (82% each). The findings suggest the need to improve physical facilities and strengthen clinical and nursing communication to maintain a consistent p Conclusion: Overall, BPJS patient satisfaction at the Orthopedic Clinic at KiSA Hospital in Depok City still needs improvement, with 55% of patients satisfied and 45% dissatisfied. The reliability and empathy dimensions are the main service strengths, while the physical and assurance dimensions show weaknesses that need to be addressed. Each dimension has its strengths and areas for improvement, for example, the accuracy of doctors' diagnoses is a strength, but the comfort of the outpatient clinic and the availability of wheelchairs are still weaknesses. Suggestion: To improve service quality, several efforts need to be made. In the reliability dimension, nurses must build trust through good communication, listen carefully to complaints, and respect patient privacy. In the assurance dimension, nurses need to be more responsive in handling complaints so that patients feel safe. In the physical dimension, hospitals are advised to conduct routine wheelchair checks at least every 6 months and improve the comfort of the clinic's outpatient rooms. In the empathy dimension, doctors need to provide more flexible consultation times for patients with complex illnesses so that complaints can be fully heard. Meanwhile, in the responsiveness dimension, the quality of the consultation process needs to be improved to make it more open and comfortable. Overall, hospitals need to conduct regular evaluations and provide space for patients to provide assessments, so that service quality can be continuously improved patient experience.